Alan Wake a psychological action thriller - Remedy Entertainment Ltd.; Microsoft Game Studios (Redmond, VA : Microsoft Game Studio, 2010)
"When the wife of the best-selling writer Alan Wake disappears on their vacation, his search turns up pages from a thriller he doesn't even remember writing. A dark presence stalks the small town of Bright Falls, Washington pushing Wake to the brink of sanity in his fight to unravel the mystery and save the woman he loves. With the body of an action game and the mind of a psychological thriller, Alan Wake is a pulse-pounding thrill ride"--Container.
Title from container.
"Xbox live"--Container.
Other features supported: game-content download, custom soundtracks, in-game Dolby Digital, voice, friends, achievements.
1 player.
ESRB rating: T, Teen (blood, language, use of alchol and tobacco, violence).
System requirements: Xbox 360 with NTSC designation; 1.65 MB to save game; HDTV 720p/1080i/1080p; hard drive required. Xbox live requires paid subscription for online multiplayer.
Keywords: Missing persons -- Computer games; Computer adventure games; Xbox 360 video games; Video games; Computer games